NEW PYRAN OF AN ENDOPHYTIC FUNGUS Fusarium sp. ISOLATED FROM THE LEAVES OF BROTOWALI (Tinaspora crispa) - Elfita Elfita; Munawar Munawar; Muharni Muharni; Suprayetno Suprayetno (Universitas Gadjah Mada, 2013)
Endophytes are microorganisms that reside asymptomatically in the tissues of higher plants and are relatively unstudied and a promising source of novel organic natural metabolites exhibiting a variety of biological activities. As a part of our systematic search for new bioactive lead structures from endophytic, the endophytic fungus Fusarium sp. isolated from the leaves of Brotowali (Tinaspora crispa), was cultured for isolation of metabolite. The endophytic fungus was cultivated on 6 L of Potatos Dextose Broth (PDB) medium at room temperature (no shaking) for 8 weeks. The cultures were then extracted with ethyl acetate to afford 9.4 g of residue after removal of the solvent under reduced pressure. The extract was separated into the fractions by column chromatography (CC) on silica gel. The fractions were further separated by silica gel column chromatography to give one compound. The molecular structure was established on the basis of spectroscopic analysis including UV, IR, 1H-NMR, 13C-NMR, HMQC, HMBC, COSY, and MS. The compound was determined as a new pyran.